Association of Race and Ethnicity and Anticoagulation in Patients With Atrial Fibrillation Dually Enrolled in Veterans Health Administration and Medicare: Effects of Medicare Part D on Prescribing Disparities. Issue 2 (February 2022) - Essien, Utibe R.; Kim, Nadejda; Magnani, Jared W.; Good, Chester B.; Litam, Terrence M.A.; Hausmann, Leslie R.M.; Mor, Maria K.; Gellad, Walid F.; Fine, Michael J.
Abstract : Background: Racial and ethnic disparities in anticoagulation exist in atrial fibrillation management in Medicare and the Veterans Health Administration, but the influence of dual Veterans Health Administration and Medicare enrollment is unclear. We compared anticoagulant initiation by race and ethnicity in dually enrolled patients and assessed the role of Medicare part D enrollment on anticoagulation disparities. Methods: We identified patients with incident atrial fibrillation (2014–2018) dually enrolled in Veterans Health Administration and Medicare. We assessed any anticoagulant initiation (warfarin or direct-acting oral anticoagulants [DOACs]) within 90 days of atrial fibrillation diagnosis and DOAC use among anticoagulant initiators. We modeled anticoagulant initiation, adjusting for patient, provider, and facility factors, including main effects for race and ethnicity and Medicare part D enrollment and an interaction term for these variables. Results: In 43 789 patients, 8.9% were Black, 3.6% Hispanic, and 87.5% White; 10.9% participated in Medicare part D. Overall, 29 680 (67.8%) patients initiated any anticoagulant, of whom 17 568 (59.2%) initiated DOACs. Lower proportions of Black (65.2%) than Hispanic (67.6%) or White (68.0%) patients initiated any anticoagulant ( P =0.001) and, lower proportions of Black (56.3%) and Hispanic (55.9%) than White (59.6%) patients ( P =0.001) initiated DOACs. Compared with White patients, Black patients had significantly lower initiation of any anticoagulant (adjusted odds ratio, 0.89 [95% CI, 0.82–0.97]). The adjusted odds ratios for DOAC initiation were significantly lower for Black (0.72 [95% CI, 0.65–0.81]) and Hispanic (0.84 [95% CI, 0.70–1.00]) than White patients. The interaction between race and ethnicity and Medicare part D enrollment was nonsignificant for any anticoagulant ( P =0.99) and DOAC ( P =0.27) therapies. Conclusions: In dually enrolled Veterans Health Administration and Medicare patients with atrial fibrillation, Black patients were less likely to initiate any anticoagulant, and Black and Hispanic patients were less likely to initiate DOACs. Medicare part D enrollment did not moderate the associations between race and ethnicity and anticoagulant therapies. Abstract : Supplemental Digital Content is available in the text.